2021
DOI: 10.3390/biomedicines9070743
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Microbiome and Stromal Cells Phenotype in Esophagus Squamous Cell Carcinoma

Abstract: Esophageal cancer is one of the most aggressive malignant neoplasms, with low survival rates and limited treatment options. In this study we analyzed the microbiome composition and the phenotype of inflammatory tumor infiltrate in squamous cell carcinoma of esophagus (ESCC) and examined possible relationships between them and their prognostic significance. We found that the predominant phyla of microorganisms found in both tumors and adjacent normal tissues were Firmicutes, Proteobacteria, Actinobacteria, Gemm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
8
0
2
Order By: Relevance
“…The literature suggests that CD163 expression is often associated with an unfavorable prognosis of various solid tumors [ 16 ]. However, for gastrointestinal tumors, it has been shown that CD163 can be a marker of good prognosis, particularly in esophageal cancer [ 17 ] and colorectal cancer [ 18 ]. For GC, an increased density of CD163+ macrophages in tumor stroma has been shown to be associated with the activation of the immune response and improved patient survival according to single-factor analysis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that CD163 expression is often associated with an unfavorable prognosis of various solid tumors [ 16 ]. However, for gastrointestinal tumors, it has been shown that CD163 can be a marker of good prognosis, particularly in esophageal cancer [ 17 ] and colorectal cancer [ 18 ]. For GC, an increased density of CD163+ macrophages in tumor stroma has been shown to be associated with the activation of the immune response and improved patient survival according to single-factor analysis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that in the case of lung and esophageal cancer, a high bacterial load in the tumor, combined with increased expression of iNOS, is a favorable prognostic factor, and a high bacterial load, combined with local immunosuppression, on the contrary, is a marker of poor prognosis [ 23 , 24 ]. Here, we demonstrate that for kidney cancer, iNOS is an independent marker of a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were divided into two groups depending on the presence of iNOS-positive cells in the stroma. Tumor staining was classified as positive when clear cytoplasmic staining was present in ≥1% of tumor cells for iNOS [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Одной из таких перспективных комбинаций может являться комплексная морфологическая оценка стромы в совокупности и бактериальной нагрузкой. Использование комплексного анализа клеточного и бактериального состава в опухоли предложено относительно недавно [53,54], однако набирает популярность [55][56][57] Дальнейшие исследования показали, что что повышенное содержание бактерий наблюдается в группах опухолей НМРЛ с высокой экспрессией iNOS в опухолевых клетках и высоким содержанием FoxP3+ стромальных Т-клеток. В целом добавление оценки общей бактериальной нагрузки в опухоли кардинально меняет картину выживаемости пациентов.…”
Section: комплексный анализ микробиома и воспалительного инфильтрата ...unclassified